Participatory Conservation for Protected Areas : An Annotated Bibliography of Selected Sources (1996-2001) - Diamond, Nancy; Nkrumah, Elisabeth; Isaac, Alan (World Bank, Washington, DC, 2014)
This report provides annotated summaries of recent publications on participatory conservation for protected areas. The report focused on lessons learned and good practices for donor-funded projects. The summaries include study objectives, methodology and findings. A keyword search list is also available at the end of the report.